2017
DOI: 10.1039/c6ra25986c
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-assisted double acoustic irradiation for concentrated aqueous dispersions of carbon nanotubes

Abstract: Carbon nanotube (CNTs) dispersion is one of the most challenging tasks for many applications. Lignin-assisted double sonication represents a low-cost and renewable alternative to prepare stable and concentrated suspensions of individualized CNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Rice straw was harvested at the South China Agricultural University in 2016. Benzene (99.5%, AR, Damao Chemical Reagent Factory, Tianjin, China), ethanol (99.7%, AR, Guangzhou Chemical Reagent Factory, Guangzhou, China), sodium chlorite (NaClO 2 , 80%, Aladdin), acetic acid glacial (CH 3 COOH, 99.5%, AR, Guangzhou Chemical Reagent Factory), potassium hydroxide (KOH, 85%, AR, Shanghai RichJoint Chemical Reagents, Shanghai, China), hydrochloric acid (HCl, 1 N, certified, Guangzhou Chemical Reagent Factory), sodium hydroxide (NaOH, 96%, Guangzhou Chemical Reagent Factory), sodium hypochlorite (NaClO, 8.0%, AR, Damao Chemical Reagent Factory), 2,2,6,6-tetramethylpyperdine-1-oxyl (TEMPO, 98%, Aladdin), sodium bromide (NaBr, 99.9%, AR, Tianjin Fuchen Chemical Reagent Factory, Tianjin, China), methylene blue (MB, AR, Tianjin Fuchen Chemical Reagent Factory), Congo red (CR, Tianjin Fuchen Chemical Reagent Factory), graphene nanoplates (GnPs, Aldrich, grade C-750, thickness: a few nm, particle size: <2 µm, specific surface area: 750 m 2 g −1 ), and OH-functionalized multi-walled carbon nanotubes (CNTs, Cheap Tubes, external diameter: 50-80 nm, internal diameter: 5-10 nm, length: 10-20 µm, OH content: 5.5%, specific surface area: 60 m 2 g −1 [30]) were used as received. The chemical formula, maximum absorption wavelength and electrical property under neutral pH of MB and CR are shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Rice straw was harvested at the South China Agricultural University in 2016. Benzene (99.5%, AR, Damao Chemical Reagent Factory, Tianjin, China), ethanol (99.7%, AR, Guangzhou Chemical Reagent Factory, Guangzhou, China), sodium chlorite (NaClO 2 , 80%, Aladdin), acetic acid glacial (CH 3 COOH, 99.5%, AR, Guangzhou Chemical Reagent Factory), potassium hydroxide (KOH, 85%, AR, Shanghai RichJoint Chemical Reagents, Shanghai, China), hydrochloric acid (HCl, 1 N, certified, Guangzhou Chemical Reagent Factory), sodium hydroxide (NaOH, 96%, Guangzhou Chemical Reagent Factory), sodium hypochlorite (NaClO, 8.0%, AR, Damao Chemical Reagent Factory), 2,2,6,6-tetramethylpyperdine-1-oxyl (TEMPO, 98%, Aladdin), sodium bromide (NaBr, 99.9%, AR, Tianjin Fuchen Chemical Reagent Factory, Tianjin, China), methylene blue (MB, AR, Tianjin Fuchen Chemical Reagent Factory), Congo red (CR, Tianjin Fuchen Chemical Reagent Factory), graphene nanoplates (GnPs, Aldrich, grade C-750, thickness: a few nm, particle size: <2 µm, specific surface area: 750 m 2 g −1 ), and OH-functionalized multi-walled carbon nanotubes (CNTs, Cheap Tubes, external diameter: 50-80 nm, internal diameter: 5-10 nm, length: 10-20 µm, OH content: 5.5%, specific surface area: 60 m 2 g −1 [30]) were used as received. The chemical formula, maximum absorption wavelength and electrical property under neutral pH of MB and CR are shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…When lignin was used as the sole coating material ( Figure 2 B), some cellulose nanofibers were still visibly exposed, meaning that lignin did not fully cover the whole paper surface. In all other cases, the absence of visible aggregates yielded relatively flat carbon layers of 25–30 μm in thickness on the paper surface regardless of the type of materials used for coating ( Figure 2 C–F), confirming the good dispersion of carbon nanomaterials during the process [ 28 , 32 ]. This can be attributed to the strong capillary forces of the porous paper, and the resulting large contact area between the coated materials and the cellulose microfibers.…”
Section: Resultsmentioning
confidence: 86%
“…Previous research reported that the flame-retardant properties of polymer composites with poorly dispersed CNTs did not improve compared to the pristine composites without CNTs [ 39 ]. Owing to its large number of condensed aromatic structures, lignin was adsorbed on GnPs and CNTs via π-π interactions and prevented the nanomaterials from sticking together due to electrostatic repulsion and steric hindrance during the aqueous-phase coating process, as demonstrated elsewhere [ 28 , 32 ]. Moreover, multiple hydrophilic groups in the lignin structure (e.g., methoxyl, phenolic hydroxyl, aldehyde and carboxyl) can interact with cellulose via hydrogen bonding, hence connecting the carbon nanomaterials to the paper substrate.…”
Section: Flame-retardant Mechanismmentioning
confidence: 99%
See 2 more Smart Citations